1994
DOI: 10.1002/pen.760341006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of warpage, global shrinkage, residual stresses, and mechanical behavior of rotationally molded parts produced from different polymers

Abstract: A comparative study of warpage, global shrinkage, and residual quench stresses developed in rotational molding is made for a series of thermoplastics including various polyethylenes, polypropylene, polyamide-6, polycarbonate, and polystyrene. The influence of rate of quench on uniaxial stress strain and impact behavior of rotomolded parts was also studied. Generally, warpage, global shrinkage, and residual stresses increase with increasing quench rate for all the polymers. Further, the levels of warpage and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 9 publications
2
18
0
2
Order By: Relevance
“…The geometry of the system has been assumed to be constant, even if during the process the polymer experiences a continuous specific volume decrease as a consequence of sintering phenomena 22,45,46 during melting and crystallization effects during cooling. 7,47,48 The numerical values of parameters listed in Eqs. (6)- (20) are shown in Table I.…”
Section: Parameter Determinationmentioning
confidence: 99%
“…The geometry of the system has been assumed to be constant, even if during the process the polymer experiences a continuous specific volume decrease as a consequence of sintering phenomena 22,45,46 during melting and crystallization effects during cooling. 7,47,48 The numerical values of parameters listed in Eqs. (6)- (20) are shown in Table I.…”
Section: Parameter Determinationmentioning
confidence: 99%
“…In earlier experimental works on RM [4][5][6], warpage has been related to cooling rate, crystallinity, and the effect of mold release agent. In [5], Bawiskar and White related warpage to residual stresses as measured by a layer removal method. Studying metallocene polyethylene (PE), Pop-Iliev et al [7] concluded that warpage increased with increasing part thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies claim that the warpage and shrinkage are related to the cooling process (Shih-Jung and Chung-Yuan, 1999;Bawiskar and White, 1994). The level of shrinkage correlates with the extent of crystallization during solidification and is minimal in vitrifying plastics according to tests performed on polyethylene, Nylon-6, polycarbonate and polystyrene (Bawiskar and White, 1994).…”
Section: General Process Descriptionmentioning
confidence: 98%